Prevalensi dan Derajat Infeksi Helminthiasis Gastrointestinal pada Sapi Bali (Bos sondaicus) di Peternakan Rakyat Mutu Desa Sepayung Kecamatan Plampang Kabupaten Sumbawa Besar Nusa Tenggara Barat - Ariandoko Ariandoko; Kholik Kholik; Candra Dwi Atma; Novarina Sulsia Ista'In Ningytas (Universitas Pendidikan Mandalika, 2021)
Bali cattle is one of the cattle that are more in demand by the community, especially the people ofSumbawa Besar. Healthy cows that are in a state or physiological body functioning normally, which meansthat cattle avoid various diseases, especially Helminthiasis. The purpose of this study was to determine theprevalence and degree of gastrointestinal helminthiasis infection in Balinese cattle (Bos sondaicus) in MutuPeople's Farms in Sepayung village, Plampang sub-district, Sumbawa Besar district, NTB. This research is adescriptive study with Based on Rates or calculation of the prevalence rate and degree of GastrointestinalHelminthiasis infection in bali cattle feces at Mutu People's Farm in Sepayung Village, Plampang District,Sumbawa Besar Regency, West Nusa Tenggara. This research was conducted in February 2020 in theLaboratory of the Faculty of Veterinary Medicine, West Nusa Tenggara University, examined using the McMaster method and counted the number of worm eggs per gram of feces. Based on the results of laboratorytests conducted on 37 bali cattle feces samples, found 6 samples infected with Trichostrongylus sp. and 2samples were infected with Ostertagia sp. The results of examinations that have been done, the prevalencefound in this study is Trychostrongylus 16.21% while in Ostertagia it is 5.40% with the degree of infection inTrichostrongylus moderate infections and in mild infections Ostertagia. Based on the results of laboratorytests conducted on 37 bali cattle feces samples, found 6 samples infected with Trichostrongylus sp. and 2samples were infected with Ostertagia sp. The results of examinations that have been done, the prevalencefound in this study is Trychostrongylus 16.21% while in Ostertagia it is 5.40% with the degree of infection inTrichostrongylus moderate infections and in mild infections Ostertagia. Based on the results of laboratorytests conducted on 37 bali cattle feces samples, found 6 samples infected with Trichostrongylus sp. and 2samples were infected with Ostertagia sp. The results of examinations that have been done, the prevalencefound in this study is Trychostrongylus 16.21% while in Ostertagia it is 5.40% with the degree of infection inTrichostrongylus moderate infections and in mild infections Ostertagia.